2008
DOI: 10.1590/s0102-86502008000700013
|View full text |Cite
|
Sign up to set email alerts
|

The role of hyperbaric oxygen therapy (HOT) as an otoprotection agent against cisplatin ototoxicity

Abstract: Purpose: Hyperbaric oxygen therapy (HOT) consists of intermittent inhalations of 100% oxygen at a pressure higher than 1 atm. It is an important adjuvant therapy in pathological processes like soft tissue infections, radiation injury, gas gangrene, osteomyelitis and decompressive diseases. Cisplatin, a potent antineoplastic drug, widely used in cancer therapy is highly ototoxic causing bilateral, irreversible damage to the hearing of high frequency sounds (4-8 KHz). Objective:This experimental study conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…35 Aydinoz et al 34 reported significant body-weight loss in cisplatin as well as cisplatin + HBO-treated rats. However, the most dramatic weight loss was observed in the cisplatin only-treated group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Aydinoz et al 34 reported significant body-weight loss in cisplatin as well as cisplatin + HBO-treated rats. However, the most dramatic weight loss was observed in the cisplatin only-treated group.…”
Section: Methodsmentioning
confidence: 99%
“…Atasoyu et al 33 have observed a high mortality rate in rats receiving cisplatin and cisplatin + HBO. Further, Yassuda et al 35 noted that 2 of 5 guinea pigs treated with combination therapy died prior to the completion of the study. Thus far, the evidence suggests that even under differing treatment conditions, combination therapy utilizing cisplatin and HBO should be avoided.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, anti-free radical agents are becoming increasingly important [4][5]. Hyperbaric oxygen (HBO) therapy, having an important antioxidant activity, is based on inhalation of 100% oxygen under pressures above 1 atm (pressurized between 1.5 and 3.0 atmosphere absolute) in a pressure chamber [7,8]. Due to its antioxidant property, HBO has been considered to prevent ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of HBO therapy in inner ear has not been still fully understood, today, it is an important adjuvant therapy and being increasingly used in a variety of disorders, such as severe anaemia, decompressive diseases, arterial gas embolism, carbon monoxide poisoning, stimulant of wound healing on refractory wounds, gas gangrene, radiation injury, necrotizing infections, and chronic osteomyelitis [7][8][9]. It has been also used in the management of acute ischemia-related disorders like acute sensorineural hearing loss such as sudden deafness, and acute noise trauma [8,[10][11][12][13][14][15]. But to the best of our knowledge, no study to date have investigated the possible protective effect of HBO against to ototoxic effect of aminoglycoside.…”
Section: Introductionmentioning
confidence: 99%
“…21 Interestingly, in an experimental study, HBO therapy results in an otoprotection effect against Cisplatin-induced ototoxicity. 22 In a series of 89 liver transplant patients, donor hyperoxygenation before organ harvest, defined as a PaO 2 value greater than 150 mmHg, was associated with good graft outcome. 23 It could be assumed that the hyperoxia preconditioning of donor has reduced liver ischemic reperfusion injury.…”
mentioning
confidence: 99%